2022
DOI: 10.1007/s00192-022-05311-5
|View full text |Cite
|
Sign up to set email alerts
|

The variation in shape and thickness of the pelvic floor musculature in males and females: a geometric-morphometric analysis

Abstract: Introduction and hypothesis In women, the risk of pelvic floor prolapse is known to be associated with age and parity. Different studies suggested that it is also related to pelvic dimensions, e.g. biomechanical modelling showed that a larger pelvic canal results in higher values of displacement, stress and strain in the pelvic floor muscles, which can increase the risk of pelvic floor disorders. To better understand the multiple factors contributing to pelvic floor disorders, we assessed how age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Thus, if the individual samples in the dataset have a vast variety of muscle morphological profiles, k‐means clustering analysis may fail to function for addressing the purpose of this study, which was to examine how individual PIFMs can be classified based on their morphological parameters. Currently, it is unknown whether morphological profiles of the PIFMs are affected by sex and/or age, but sex differences have been found to exist in other muscles such as those in the lower/upper extremities [20–22] and around the pelvis [40]. Thus, more studies are needed to further examine sex differences in morphological profiles of the PIFMs and the applicability of the current results to other populations, such as females.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, if the individual samples in the dataset have a vast variety of muscle morphological profiles, k‐means clustering analysis may fail to function for addressing the purpose of this study, which was to examine how individual PIFMs can be classified based on their morphological parameters. Currently, it is unknown whether morphological profiles of the PIFMs are affected by sex and/or age, but sex differences have been found to exist in other muscles such as those in the lower/upper extremities [20–22] and around the pelvis [40]. Thus, more studies are needed to further examine sex differences in morphological profiles of the PIFMs and the applicability of the current results to other populations, such as females.…”
Section: Discussionmentioning
confidence: 97%
“…A further limitation of our study is the retrospective study design with imaging not originally undertaken for morphometric research purposes. Larger patient collectives will be needed to gain normative values for the LAM muscle in healthy nulliparous women, corrected for pelvic size, gender and ethnicity [29]. Studies have reported differences in the bony architecture of the pelvis in women with and without pelvic floor disorders as well as between different ethnic groups [30,31].…”
Section: Discussionmentioning
confidence: 99%